Phytoparasitic nematodes in broad bean crops in eastern Puebla - Núñez-Sánchez, Ángel Enrique; Núñez-Camargo, María del Carmen; Vázquez-González, Carlos Yair; Salinas-Castro, Alejandro; López-Lima, Daniel (Revista Mexicana de Ciencias Agrícolas, 2024)
The broad bean is one of the most important crops in the Central Mexican Plateau due to its adaptation to edaphoclimatic conditions and its high nutritional value in the diet of the inhabitants of this region. Nonetheless, the yields obtained are low compared to the world average. Phytoparasitic nematodes are one of the main constraints to broad bean production in other parts of the world; however, its presence in this crop is unknown in Mexico. In this work, phytoparasitic nematodes associated with broad bean crops were identified and quantified in 10 farms in the municipalities of Tepeyahualco and Cuyoaco, Puebla, and in plants germinated in sterile soil from seeds from different areas in 2022. The following six genera of phytoparasitic nematodes were found: Criconemoides, Ditylenchus, Helicotylenchus, Hoplolaimus, Pratylenchus and Zygotylenchus. The most abundant genera were Ditylenchus and Pratylenchus, with a population density of 11 and 7 specimens per 100 cm3 of soil and 159 and 60 specimens per 100 g of plant tissue, respectively, and they were found in all sampling sites. The population density of Ditylenchus exceeds the economic threshold of the crop; in addition, specimens of this genus were found in plants germinated in sterile soil. The results show that Ditylenchus is distributed throughout the sampled area and can affect yield. Further studies are needed to determine the identity of nematode species and their distribution in other production areas.
Keywords: Ditylenchus; Pratylenchus; Vicia faba; detection